Effect of fin efficiency models on air-side performance of crimped spiral fin-and-tube heat exchangers - Kiatpachai, Parinya; Suksangpanomrung, Anotai; Thiangtham, Phubate; Keepaiboon, Chanyoot; Duangthongsuk, Weerapun; Wongwises, Somchai (SAU JOURNAL OF SCIENCE & TECHNOLOGY, 2018)
In this study, we investigate the effect of fin efficiency (hf) models on the airside performance (ASPs) of crimped, spiral fin and tube heat exchangers (SHXs). The analysis of ASP is calculated using different fin efficiency models based on the assumptions of constant heat flux for each Reynolds number, constant heat transfer area with negligible fin thickness, and constant fin geometry for four exanimate heat exchangers (HX). The L-Rectangular, L-Convex, L-Triangular, and L-Concave models of longitudinal fin efficiency are used in the calculation and compared with the R-Rectangular model for radial fin efficiency that looks more realistic than the tested crimped spiral fin. The four samples are the crimped SHX. The well-insulated, open wind tunnel is used for heat transfer between two working fluids, i.e., ambient air and hot water. The experiment is carried out over a range of Vfr (1-6 m/s) or Redo of 3,000 to 12,000. The results show that the L-Triangular, L-Convex, and L-Rectangular models for fin efficiency provide trends of heat transfer coefficients that are more similar to the realistic R-Rectangular model. However, we found another model over-predicting the heat transfer coefficient by as much as 5-10%. This model uses the L-Concave model of fin efficiency with various Cu and Al fins, each with 3 or 4 tube rows. Moreover, we demonstrate a similar trend and value for fin efficiency between L-Triangular and R-Rectangular models. The effect of fin efficiency models and fin materials has a strong variation in terms of fin efficiency. In contrast, the number of tube rows, whether 3 or 4, has no significant effect on fin efficiency. This proposed research can be generally applied to selection of a model by fin efficiency and prediction of safety factors in designing crimped SHX.